RAGAM STRATEGI AL’AB LUGHAWIYAH PEMBELAJARAN BAHASA ARAB DI SDIT AL-FITYAH KOTA SOLOK - Fakhrin, Nurul; Alrasi, Fitri; Wahdi, Rifana; Pratiwi, Sekar Harum (Prodi PGMI STIT Sunan Giri Bima, 2024)
This research was motivated by difficulties in understanding Arabic language learning by class III students at SDIT Al-Fityah, Solok City, which was caused by students' interest and motivation towards learning Arabic so that student learning outcomes were far from what was expected. Therefore, a teacher must correctly choose and determine Arabic language learning strategies. When teachers do not correctly determine learning strategies, this will of course make it difficult for the learning process and the achievement of learning objectives. Various al'ab allughawiyah strategies used in the learning process will be reviewed. Apart from that, it will be adapted to learning practices, so that we can see what the results are when Al’ab lughawiyah is applied to the learning process in class III of SDIT Al-Fityah, Solok City. The process of data collection and data analysis in this research was carried out in a qualitative descriptive manner. The results of this research show that students in class III SDIT Al-Fityah, Solok City show better learning outcomes and the grades obtained by students increase.